Pemeriksaan Inspeksi Visual Asetat (IVA) Dan Pemeriksaan Payudara Secara Klinis (SADANIS) Di Posbindu Secara Mobile - Achmad, Feni Yunia; Hasinuddin, M.; Anggraeni, Novi; Moeldjono, Eddy; Amriani, Amriani (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2025)
In Indonesia, screening using the IVA technique is only performed by 6.83% of women aged 30-50 years. The coverage of cervical cancer screening in Indonesia is still below the target of 70% in 2023, which is only 7.02%. This study aims to compare the frequency of visits by women of childbearing age for IVA and sadanis examinations before and after the innovation of the IVA and sadanis examination movement at the mobile Posbindu. The sample for this innovation was 55 through simple random sampling. The results of data analysis using the t-test obtained sig = 0.000, this means it is smaller than α = 0.05. Thus, Ho is rejected and Ha is accepted. There is an increase in visits by women of childbearing age for IVA and sadanis examinations before and after the innovation of the IVA and sadanis examination movement at the mobile Posbindu.